Emergency remote teaching of English as a foreign language during COVID-19: Perspectives from a university in China - Huang, Min; Shi, Yahui; Yang, Xiaoqiong (IJERI: International Journal of Educational Research and Innovation, 2020)
Given the circumstances of the global pandemic, universities around China and across the globe have suspended face to face (F2F) classes and transitioned to emergency remote teaching (ERT). University students in China have been the first to go through the whole semester’s ERT including College English, a compulsory language course for almost all the first- and second-year students of non-English majors. This article adopted a mixed-methods design, a survey followed by a qualitative visual method, gathered data on students’ experience about ERT of College English and presented an investigation into detailed interactive process of the classes. The data analysis on the learners’ engagement and the feedback from the learners provided a summary of the key threads of ERT classes. This study demonstrated that students held an extrinsic goal orientation, which did not differ from their face-to-face learning experience. ERT granted students more opportunities for interaction with their instructor and peers, while collaboration among students were limited. The research results can be connected to the larger fabric of global language teaching in crisis context, provide empirical lessons to educators, and help instructors with their future decision-making about technology-supported activities.